Selection for Drinking in the Dark Alters Brain Gene Coexpression Networks - Iancu, Ovidiu Dan (2013)
BACKGROUND: Heterogeneous stock (HS/NPT) mice have been used to create lines selectively bred in replicate for High Drinking in the Dark (HDID) (Crabbe et al., 2009; Crabbe et al., 2011b). Both selected lines routinely reach a blood ethanol concentration of 1.00 mg/ml or greater at the end of the day 2 four hour period of access. The mechanisms through which genetic differences influence DID are currently unclear. Therefore, the current study examines the transcriptome, the first stage at which genetic variability affects neurobiology. Rather than focusing solely on differential expression, we also examine changes in the ways that gene transcripts collectively interact with each other, as revealed by changes in coexpression patterns. METHODS: Naïve mice (N=48/group) were genotyped using the Mouse Universal Genotyping Array, which provided 3683 informative markers. QTL analysis used a marker-by-marker strategy with the threshold for a significant LOD set at 10.6. Gene expression in the ventral striatum was measured using the Illumina Mouse 8.2 array. Differential gene expression and the Weighted Gene Coexpression Network Analysis (WGCNA) were implemented largely as described elsewhere (Iancu et al., 2010; Iancu et al., 2012b). RESULTS: Significant quantitative trait loci (QTLs) for elevated blood ethanol concentrations after DID were detected on chromosomes 4, 14 and 16; the latter two were associated with gene poor regions. None of the QTLs overlapped with known QTLs for ethanol preference drinking. Ninety- four transcripts were detected as being differentially expressed in both selected lines vs HS controls; there was no overlap with known preference genes. The WGCNA revealed 2 modules as showing significant effects of both selections on intramodular connectivity. A number of genes known to be associated with ethanol phenotypes (e.g. Gabarg1, Glra2, Grik1, Npy2r and Nts) showed significant changes in connectivity. DISCUSSION: We found marked and consistent effects of selection on coexpression patterns; differential expression changes were more modest and less concordant. The QTLs and differentially expressed genes detected here are distinct from the preference phenotype (Mulligan et al., 2006). This is consistent with behavioral data and suggests that the DID and preference phenotypes are markedly different genetically.